Effect of thymol on properties of bionanocomposites from poly (lactic acid)/poly (butylene succinate)/nanofibrillated cellulose for food packaging application - Zabidi, Nurul 'Afifah; Zainal, Nur Najiha; Mohamed Amin Tawakkal, Intan Syafinaz; Mohd Basri, Mohd Salahuddin; Ariffin, Siti Hajar; Naim, Mohd Nazli (Elsevier, 2023)
The present study developed the formulation of active bionanocomposites films endowed with the abilities of high biodegradability and antimicrobials for active packaging applications. The aim of this work was to prepare poly (lactic acid)/poly (butylene succinate) (PLA/PBS) blended films reinforced with different concentrations of nanofibrillated cellulose (NFC) and 9 % of thymol essential oil (EO) using the casting method. The active films were further evaluated through Fourier transform infrared spectroscopy (FTIR); as well as mechanical, physical, water vapour permeability (WVP), thermal analysis (TGA), biodegradation, morphological, and antimicrobial (% reduction of bacteria) testing. The tensile strength (TS) of PLA/PBS blend films increased by 12 % with the incorporation of 2 wt% of NFC. The PLA/PBS/NFC with 9 % thymol EO has a good water barrier performance with its tensile strength, elongation at break, and tensile modulus was 13.2 MPa, 13.1 %, and 513 MPa respectively. The presence of NFC promoted the disintegration of PLA/PBS films by 70.5 %. These films promoted the antibacterial activity against S. aureus and E. coli. The study demonstrates that the developed films improved the qualities of chicken fillets and have great potential to be used as active bionanocomposites in food packaging applications.